2022
DOI: 10.1111/wej.12820
|View full text |Cite
|
Sign up to set email alerts
|

Cationic lignin polymers as flocculants for municipal wastewater

Abstract: In this research, two lignin-[2-(methacryloyloxy)ethyl]trimethylammonium chloride (METAC) polymers were generated and assessed for their efficiency in treating municipally produced wastewater. The removals of chemical oxygen demand (COD) and turbidity were 47.5% and 71.2%, respectively, for the singular flocculation system at the dosage of 40-70 mg/L. For the dual coagulation/flocculation system, the polymer with a higher charge density (AM2) achieved higher COD and turbidity removals than the polymer with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Flocculation is a form of coagulation, when fine suspended dispersed particles in a liquid or gaseous medium form loose flocculated clusters, i.e., floccules. Natural [36,37] and synthetic water-soluble polymers [38,39] and their polycomplexes [40,41] are used as flocculants for raw water treatment.…”
Section: Coagulation and Flocculationmentioning
confidence: 99%
“…Flocculation is a form of coagulation, when fine suspended dispersed particles in a liquid or gaseous medium form loose flocculated clusters, i.e., floccules. Natural [36,37] and synthetic water-soluble polymers [38,39] and their polycomplexes [40,41] are used as flocculants for raw water treatment.…”
Section: Coagulation and Flocculationmentioning
confidence: 99%
“…Flocculation is a form of coagulation, when fine suspended disperse particles in a liquid or gaseous medium, form loose flocculated clusters, i.e., floccules. Natural [35,36] and synthetic water-soluble polymers [37,38] and their polycomplexes [39,40] are used as flocculants for raw water treatment.…”
Section: Coagulation and Flocculationmentioning
confidence: 99%
“…In recent years, graft copolymerization has been frequently used to prepare various environmentally friendly lignin-based flocculants with improved flocculation performance. Moore et al [ 18 ] synthesized a cationic hydrolyzed lignin polymer using free-radical polymerization with [2-(methacryloyloxy)ethyl] trimethylammonium chloride (METAC) and hydrolysis lignin (HL) and then examined the flocculation efficiency of the lignin-based flocculants in simulated wastewater. Their results indicated that HL-METAC could remove up to 60% of the TOC present.…”
Section: Introductionmentioning
confidence: 99%